(untitled) - Burley, T. M. (London, 1973)
This book provides a valuable appraisal of the economic and social geography of the Philippine.
Keywords: Philippines,Philippines,Phi Luật Tân,Phi Luật Tân; Economic conditions,Social conditions,Điều kiện kinh tế,Điều kiện xã hội